Combining solar power with coal-fired power plants, or cofiring natural gas. Issue 1 (7th March 2018) - Mills, Stephen
Abstract: Coal-fired power operators continue to look for ways to increase the efficiency and extend the working lives of their plants by improving operational flexibility and reducing environmental impact. Two possible options are explored here: combining solar energy with coal-fired power generation, and cofiring natural gas in coal-fired plants. Both techniques show potential. Depending on the individual circumstances, both can increase the flexibility of a power plant whilst reducing its emissions. In some cases, plant costs could also be reduced. Clearly, any solar-based system is limited geographically to locations that receive consistently high levels of solar radiation. Similarly, although many coal-fired plants already burn limited amounts of gas alongside their coal feed, for cofiring at a significant level, a reliable, affordable supply of natural gas is needed. This is not the case everywhere. But for each technology, there are niche and mainstream locations where the criteria can be met. The need for good solar radiation means that the uptake of coal-solar hybrids will be limited. Cofiring natural gas has wider potential: currently, the largest near-term market appears to be for application to existing coal-fired plants in the USA. However, where gas is available and affordable, potential markets also exist in some other countries.